2018
DOI: 10.1111/pce.13136
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of selected FASCICLIN‐LIKE ARABINOGALACTAN PROTEIN genes associates with the abortion of kernels in field crops of Zea mays (maize) and of Arabidopsis seeds

Abstract: Abortion of fertilized ovaries at the tip of the ear can generate significant yield losses in maize crops. To investigate the mechanisms involved in this process, 2 maize hybrids were grown in field crops at 2 sowing densities and under 3 irrigation regimes (well-watered control, drought before pollination, and drought during pollination), in all possible combinations. Samples of ear tips were taken 2-6 days after synchronous hand pollination and used for the analysis of gene expression and sugars. Glucose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 82 publications
2
16
0
Order By: Relevance
“…In a third example, in maize the expression level of group A ZmFla genes was inversely correlated with seed abortion. Consistently, two different mutations in the group A AtFla9 locus that showed abnormally low and high AtFla9 RNA levels displayed increased and decreased seed abortion, respectively [ 169 ]. Lastly, a comparative study of 30 different wheat ( Triticum aestivum ) varieties found an association between the expression of a FAS1 protein and grain milling properties [ 170 ].…”
Section: Biological Functions Of Plant Fasciclin 1 Proteinsmentioning
confidence: 85%
“…In a third example, in maize the expression level of group A ZmFla genes was inversely correlated with seed abortion. Consistently, two different mutations in the group A AtFla9 locus that showed abnormally low and high AtFla9 RNA levels displayed increased and decreased seed abortion, respectively [ 169 ]. Lastly, a comparative study of 30 different wheat ( Triticum aestivum ) varieties found an association between the expression of a FAS1 protein and grain milling properties [ 170 ].…”
Section: Biological Functions Of Plant Fasciclin 1 Proteinsmentioning
confidence: 85%
“…Plant FLAs are also proposed to interact with wall polysaccharides and CWI sensors suggesting they play comparable roles to that of animal FAS1 proteins. A role in stress responses is supported by phenotypes of a number of fla mutants, including salt overly sensitive5 ( sos5 ) which revealed a role for FLA4/SOS5 in CWI during salt stress [150] and fla9 mutants which show an increased seed abortion phenotype during drought stress [157].…”
Section: Cell Wall Integrity As a Measure Of Stressmentioning
confidence: 99%
“…FLAs can also regulate pollen development. In Arabidopsis and maize, AtFLA9 and ZmFLA7 showed negative correlation with abortion, and reductions in the expression of FLAs increased the abortion of fertilized ovaries [23]. AtFLA3-silenced Arabidopsis had abnormal pollen grains, also suggesting a function in pollen formation [24].…”
Section: Introductionmentioning
confidence: 98%